Sri Lankan Housemaids in Lebanon A Case of 'Symbolic Violence' and 'Everyday Forms of Resistance' - Moukarbel, Nayla (IMISCoe Dissertations, 2009)
Unraveled in this book are the real dynamics at stake in the Madame/housemaid relationship. While cases of extreme physical abuse by the Lebanese women who hire housemaids - Madames - are an exception, what has become normalised are more insidious patterns of domination used to control each and every aspect of their employees' lives. For their part, Sri Lankan housemaids are not merely passive victims. Away from direct provocation and first-hand repercussions, they try to deflect what Pierre Bourdieu has called 'symbolic violence'. These attempts at 'everyday forms of resistance', as defined by James Scott, can help loosen their employers' grip. Yet, as this unprecedented study shows, the Madame/housemaid relationship and the rules that govern it remain under the managerial hold of the Madame.